Women diagnosed with endometriosis show high serum levels of diethyl hexyl phthalate - Sadia Nazir; Zeenat Usman; Muneer Imran; Khalid Pervaiz Lone; Gulfam Ahmad (Wolters Kluwer Medknow Publications, 2018)
Background: Endometriosis is one of the common causes of infertility with very diverse etiology. In modern lifestyle, humans are exposed to several endocrine-disrupting chemicals (EDCs) which may lead to reproductive disturbances. Diethyl hexyl phthalate (DEHP) is one of the common EDCs to which women are exposed by the use of cosmetics, perfumes, food packaging, medicine, and insecticides. Aim: The aim of this study was to measure the levels of DEHP in women diagnosed with endometriosis and healthy females and to compare these levels among different stages of endometriosis. Setting and Design: This descriptive study was conducted at a tertiary care hospital. Subjects and Methods: This study comprised of fifty women diagnosed with endometriosis, aged 20-40 years, and fifty age-matched healthy, fertile women without endometriosis. Females on any medication/comorbid conditions were excluded from the study. Serum DEHP concentrations were measured by high-performance liquid chromatography (HPLC). The results were expressed as means ± standard deviation (SD) (ng/ml of DEHP). Statistical Analysis: Data were analyzed using IBM-SPSS version 20. Two-sample Student's t-test and one-way ANOVA were applied for the analysis. Results: The mean ± SD value of DEHP in cases was 65.29 ± 21.69 ng/ml; however, the mean ± SD value of DEHP in controls was undetectable. Comparison of DEHP among stages of endometriosis revealed an increasing trend with advanced stages (III and IV). The values were not different between the two age groups of women with endometriosis (20-30 and 31-40 years). Conclusion: High levels of DEHP in women diagnosed with endometriosis suggest a role of phthalates in the etiology of endometriosis and permit careful use of such compounds.